Kids at the Crossroads: The Influence of International Law on Child Psychology - Butt, Junaid Sattar; Kousar, Farzana (Acta Universitatis Danubius. Juridica, 2025)
This research explores the intersection of international law and child psychology, emphasizing how legal frameworks shape the mental health and well-being of children across diverse cultural contexts. The Court has established that private life comprises physical and psychological elements and relates to a person’s identity. Focusing on key instruments such as the UN Convention on the Rights of the Child, the study examines the implications of these laws for psychological practices and policies affecting children’s rights and welfare. Through a review of case studies and existing literature, we highlight the positive impacts of international legal standards on child mental health interventions, as well as the challenges faced in their implementation. By analyzing the role of cultural variations and local practices, the research underscores the necessity for collaboration between legal and psychological professionals to advocate for effective, child-centered approaches. Ultimately, this study aims to illuminate the critical role of international law in shaping a more supportive environment for children’s psychological development, suggesting pathways for future research and policy improvements.